Theory of the distribution of city sizes: Review and prospects - Richardson, Harry W. (Regional studies, 1973)
Richardson H. W. (1973) Theory of the distribution of city sizes: Review and prospects, Reg. Studies 7, 239-251. The distribution of city sizes may be represented by any one of three similar statistical relationships: the lognormal, Pareto and ranksize distributions. This paper surveys existing and suggests new theories capable of generating one or more of these distributions. The types of theory analysed include hierarchy, stochastic, economic and allometric growth models. Specific attention is focused on two new possibilities, Markov chain models of interurban migration and capital flows and a simultancously multiplicative theory. However, the predictions of all the models are too insensitive for any one to be preferred via comparison of actual and predicted size distributions. A satisfactory explanation probably needs to draw upon both systematic and stochastic factors.